Deteriorations in physical qualities during a 10-week unsupervised off-season period in academy rugby union players - Twist, C.; Williams, J.; Dobbin, N. (Science and Medicine in Football, 2022)
Purpose: To determine the changes in physical qualities of academy rugby union players over a 10-week unsupervised off-season period. Methods: Body mass, jump height, sprint performance, and intermittent running (30:15 IFT) of 64 academy rugby union players (age = 17.2 ± 0.4 y) were recorded before and after the off-season. Results: Changes in body mass (+1.4 ± 1.3 kg), countermovement jump (-2.2 ± 1.2 cm), squat jump (-1.5 ± 1.8 cm), 10 m sprint (+0.06 ± 0.05 s), 40 m sprint (+0.13 ± 0.11 s) and 30:15 IFT (-0.8 ± 0.8 kmŸh-1) were observed (P < 0.001, d = -1.77 to 0.47). Only changes in body mass were greater in forwards than backs (P = 0.036, d = 0.46). Players with higher end-of-season body mass, squat jump and 30:15 IFT had greater off-season changes (P = < 0.001 to 0.044; d = 0.63 to 0.94), whilst the pre-post difference in body mass influenced CMJ (P = 0.005, d = 0.75) and 10 m momentum change (P < 0.001, d = 1.61). Conclusion: Understanding the individuality of the changes in physical qualities of academy rugby union players during the off-season is important to ensure players return safely to pre-season training loads.